2017
DOI: 10.1200/jco.2016.71.9096
|View full text |Cite
|
Sign up to set email alerts
|

Clonal History and Genetic Predictors of Transformation Into Small-Cell Carcinomas From Lung Adenocarcinomas

Abstract: Purpose Histologic transformation of EGFR mutant lung adenocarcinoma (LADC) into small-cell lung cancer (SCLC) has been described as one of the major resistant mechanisms for epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). However, the molecular pathogenesis is still unclear. Methods We investigated 21 patients with advanced EGFR-mutant LADCs that were transformed into EGFR TKI-resistant SCLCs. Among them, whole genome sequencing was applied for nine tumors acquired at various time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
347
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(409 citation statements)
references
References 31 publications
37
347
3
1
Order By: Relevance
“…NOTCH alterations promote ASCL1 and CD56 overexpression (9). These changes induce cyclin-dependent kinase 5 (CDK5) activity and inactivation of RB by phosphorylation (9). The present study reports a case of acquired resistance to icotinib therapy through transformation to SCLC.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…NOTCH alterations promote ASCL1 and CD56 overexpression (9). These changes induce cyclin-dependent kinase 5 (CDK5) activity and inactivation of RB by phosphorylation (9). The present study reports a case of acquired resistance to icotinib therapy through transformation to SCLC.…”
Section: Introductionmentioning
confidence: 87%
“…The most studied signaling pathway is the achaete-scute homolog 1 (ASCL1) which is regulated by four different neurogenic locus notch homolog (NOTCH) receptors. NOTCH alterations promote ASCL1 and CD56 overexpression (9). These changes induce cyclin-dependent kinase 5 (CDK5) activity and inactivation of RB by phosphorylation (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al have recently described predictors of transformation into small-cell carcinomas from lung adenocarcinomas under treatment by tyrosine kinase inhibitor (1). Their very interesting work raises several reflections about tumor transformation and the clinical management of tumor drug resistance.…”
mentioning
confidence: 99%
“…The article by Lee et al provides important advancements about the pathogenesis of such mechanism of EGFRinhibitor resistance (1). Through the genomic analysis of repeat biopsy of patients diagnosed with EGFR-mutated lung adenocarcinoma, the authors found that the alterations of the cancer gene drivers RB1 and TP53 are present even in early stage lung adenocarcinoma.…”
mentioning
confidence: 99%